Development of methods for optimisation of complex 3D weave geometries - Spackman, G.H.; Brown, L.P.; Jones, I.A. (2018)
The development of 3D weaves has resulted in the ability to produce near net shaped preforms, with the additional advantage over unidirectional lay-ups and 2D weaves of greater delamination resistance provided by through-thickness reinforcement. 3D weaving can allow the post-weave formation of bifurcations to form the web and flange of structural components. The mechanical properties of 3D woven components are highly dependent on the weave architecture, allowing the mechanical performance of the component to be tailored to its specific application. Given the number of design parameters to be varied, the design space is potentially infinite. This work focuses on the development of methods to find the optimum weave geometry of a unit cell based on the numerical evaluation of objective functions. This work demonstrates the development of methods to optimise 3D woven textile geometry, using the University of Nottingham’s open-source software TexGen [1] to automatically generate each weave based on the input from a global optimisation algorithm. Methods of varying a number of the parameters will be reported alongside their geometric and physical constraints. Finally, the facility to automatically generate a wide range of weaves, with the ability to vary parameters as desired for input either directly into an optimisation algorithm or for further pre-processing is demonstrated.